UPAYA MENGEMBANGKAN KECERDASAN MAJEMUK ANAK MENGGUNAKAN METODE AUDIO VISUAL DAN PERMAINAN TRADISIONAL DI TK AL AZHAR 6 - Retno Zen Astuti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Multiple intelligences are different types of intelligence that each person has. A child can have intelligence that is different from other children. In the theory of multiple intelligences proposed by Gardner, everyone has different types of intelligence. Gardner divides it into eight types of intelligence. One of the activities that can develop multiple intelligences is the activity of playing motion and songs as well as outdoor playing activities using audio-visual media in the form of laptops and small sounds and traditional games. Early Childhood Education (PAUD). One period to the start Its hallmark is the Golden Age, at which time all the potential is most rapidly growing child. One way to increase a child's potential from an early age is to play. Because the slogan of early childhood education is